Chilean Gastric Cancer Task Force: A study protocol to obtain a clinical and molecular classification of a cohort of gastric cancer patients. Issue 16 (April 2018) - Owen, Gareth I.; Pinto, Mauricio P.; Retamal, Ignacio N.; Fernádez, María F.; Cisternas, Betzabe; Mondaca, Sebastian; Sanchez, Cesar; Galindo, Hector; Nervi, Bruno; Ibañez, Carolina; Acevedo, Francisco; Madrid, Jorge; et al.
Abstract : Abstract: Gastric cancer (GC) is the world's second-leading cause of neoplastic mortality. Genetic alterations, response to treatments, and mortality rates are highly heterogeneous across different regions. Within Latin America, GC is the leading cause of cancer death in Chile, affecting 17.6 per 100, 000 people and causing >3000 deaths/y. Clinical outcomes and response to "one size fits all" therapies are highly heterogeneous and thus a better stratification of patients may aid cancer treatment and response. The Gastric Cancer Task Force is a Chilean collaborative, noninterventional study that seeks to stratify gastric adenocarcinomas using clinical outcomes and genomic, epigenomic, and protein alterations in a cohort of 200 patients. Tumor samples from the Pathology Department and the Cancer Center at UC-Christus healthcare network, Pontificia Universidad Católica de Chile will be analyzed using a panel of 143 known cancer genes (Oncomine Comprehensive Assay) at the Center of Excellence in Precision Medicine in Santiago, Chile. In addition, promoter methylation for selected genes will be performed along with tissue microarray for clinically relevant proteins (e.g., PD-L1, Erb-2, VEGFR2, among others) and Helicobacter pylori and Epstein–Barr virus status. Obtained data will be correlated to 120 clinical parameters retrieve from medical records, including general patient information, cancer history, laboratory studies, comorbidity index, chemotherapy, targeted therapies, efficacy, and follow-up. The development of a clinically meaningful classification that encompasses comprehensive clinical and molecular parameters may improve patient treatment, predict clinical outcomes, aid patient selection/stratification for clinical trials and may offer insights into future preventive and/or therapeutic strategies in patients from Latin America region. Trial registration: ClinicalTrials.gov Identifier: NCT03158571, Registered on May 18, 2017. Abstract : Supplemental Digital Content is available in the text